Deep Brain Stimulation in Treatment-Resistant Depression: A Systematic Review and Meta-Analysis on Efficacy and Safety - Wu, Youliang; Mo, Jiajie; Sui, Lisen; Zhang, Jianguo; Hu, Wenhan; Zhang, Chao; Wang, Yao; Liu, Chang; Zhao, Baotian; Wang, Xiu; Zhang, Kai; Xie, Xuemin (Frontiers in Neuroscience, 2021)
Objective: Deep brain stimulation (DBS) has shown promising outcomes as new therapeutic opportunities for patients with treatment-resistant depression (TRD) who do not respond adequately to several consecutive treatments. This study aims to systematically review and conduct a meta-analysis on the efficacy and safety of DBS for TRD. Method: The literature was comprehensively reviewed using Medline, Google scholar, Cochrane library, Embase and World Health Organization International Clinical Trials Registry Platform until January 2019. The studied outcomes included response, remission, recurrence and adverse events (AEs) rates, and were reported as the rate ratio (RR) or pooled estimate with a 95% confidence interval (95% CI). Heterogeneity was measured by an I-square test and a sensitive analysis. Results: A total of 17 studies involving 7 DBS targets were included. For efficacy, DBS treatment was statistically benefit for TRD, and the response, remission, and recurrence rates were 56% (ranging from 43% to 69%), 35% (ranging from 27% to 44%) and 14% (ranging from 4% to 25%), respectively. However, only two randomized-controlled trials (RCTs) considered the invalidity of DBS (RR = 1.45, 95% CI = 0.50 to 4.21). For safety, the AEs rate was 67% (ranging from 54% to 80%). The AEs were common and moderate, but the problems related to suicide and suicidal ideation should not be underestimated. Conclusion: These findings suggest that DBS for TRD is considered promising, which should be confirmed by well-designed and large sample studies. Future basic research and comprehensive clinical trials are needed to reach better understanding on the mechanisms of action and optimal targeted structure.